Analisis Kelembagaan dan Srategi Peningkatan Daya Saing Komoditas Kentang di Kabupaten Banjarnegara, Jawa Tengah - Ruwanti Eka Rahayu; Lindawati Kartika (Institut Pertanian Bogor, 2015)
The increase of import volume and the decrease of export volume of vegetables require the efforts to increase the competitiveness of local vegetable products. Potato is the core of highland vegetable commodities in national and regional areas that potential to be developed. One of the potatoes production centers in Central Java is Banjarnegara Regency. The purpose of this study are to formulate strategy and key performance indicators (KPIs) that will increase the competitiveness of potato in Banjarnegara. Data analyzed by Descriptive analysis, TOWS analysis, and Pairwise Comparison. The results of this study indicate that: the KPIs that become the priorities in increasing the competitiveness of potato in Banjarnegara are; a) The number of farmers who distribute their products in cooperative; b) Percentage increase in the number of certified seed potatoes that meet farmer’s needs; and c) Percentage increase of the local potatoes production to meet the demand of domestic and export markets as well as the related regulations on potatoes business partnership contract system.